Media and Drug Abuse: A Critical Assessment of the Role of Newspapers in Curbing Drug Abuse among Youth in Nigeria - Wonuola, Monsurat (Media and Communication Review, 2024)
The youth in Nigeria is bedeviled with series of crime-related activities, such as malpractice, bullying, and drug abuse among others. Drug abuse is the mother of all crimes since it is believed to have the power of making people temporary insane. Mass media as a change agent is saddled with the responsibility to influence societal values in order to uphold national integrity. However, there is an alleged accusation against the Nigerian mass media that it is yet to properly educate youth on the danger inherent in drug abuse. Hence, the current study aimed to explore the newspapers’ role in curbing drug addiction among the Nigerian youth. The study was underpinned by agenda setting and framing theories. Quantitative content analysis and discourse analysis were employed to examine The Punch and Daily Trust newspapers published between January 1st and March 31st, 2024. The findings revealed that the Nigerian newspapers condemned the drug menace among youth by focusing more on security implications of drug abuse with little attention paid to societal and health implications of the menace. The study concluded that the Nigerian newspapers play a critical role in enlightening people pertaining to the security threat that accompany the drug abuse among youth. Furthermore, the study recommended that the Nigerian newspapers should employ interpretative approach to drug abuse reporting since this may orient the youth on the danger inherent in the menace. This if done, may empower the youth thereby, enhancing orderliness, national development, and national security in Nigeria